PENGUATAN PARTISIPASI PEREMPUAN DALAM PEMBANGUNAN DI KELURAHAN BIROBULI SELATAN KOTA PALU - Syahruddin Hattab; Daswati Daswati; Rachmad Rachmad (JURNAL AKADEMIK PENGABDIAN MASYARAKAT, 2024)
The implementation of community service activities was carried out in the South Birobuli Village, Palu City. It is planned to be implemented in July 2024. Targeting the residents of the South Birobuli Village, especially women, this socialization and community service aims to be able to provide stimulation to women to further increase their level of participation in development. The role of women is no less important than the role of men so that equality of function and role is the same in advancing regional development, especially in the South Birobuli Village, South Palu District, Palu City.The expected outputs of this community service are, first, increasing women's understanding through the results of the socialization carried out. The socialization activity is expected to provide a better understanding of the importance of women's participation in development. Second, the results of this community service can be published in a national community service journal to share knowledge and experience with other parties.